Extradural Spinal Tumors: Report of 36 Cases and Review of Literature (Nepal Journal of Neuroscience, 2016)
About 55% of spinal tumors are extradural arising from vertebral bodies, epidural and surrounding neural and soft tissues. More than 90% of extradural spinal tumors are metastatic lesions. Extradural spinal tumors are common cause of back pain, sensory motor deficit and sphincters dysfunction. The wide range of lesions and varied clinical profile, make management of spinal extradural tumors a challenging task for any neurosurgeon.Aim of this study is to analyze and discuss the results of extradural spinal tumors after surgical treatment and relevant literature will be reviewed.This is a retrospective study of 36 patients who were operated for spinal extradural tumors between May 1999 and December 2012 in our institute.Follow up period ranged from 3 years to 12 years. Functional neurological outcome was assessed by McCormick's grading. There were 20 male and 16 female and age ranged from 10 to 80 years. 30 patients presented with back pain and 15 had radicular pain. On presentation 18 patients had motor sensory deficit and 15 had sphincters dysfunction. Most common involved level of spines were thoracic followed by cervical and lumbar.Gross total excision of masses were carried out in all cases. Common pathologies were neurofibromas (16), Ewing's sarcoma (7), granulomas (3), metastatic lesions (2), angiolipoma (2), chondroma (2), aneurysmal bone cyst (1), plasmacytoma (1), rabdomyosarcoma (1) and neuroblastoma (1).Out of 14 patients who harbored malignant pathology 12 patients received radio and chemotherapy. Post operative wound infection occurred in 5 patients. Regarding post operative neurological status, 18 patients showed improvement, 6 patients remained same and 12 patients had deteriorated neurology. Tumor recurrence occurred in 15 patients; 12 patients with malignant and 3 patients with benign lesions on follow up period. There was no surgery related mortality, however, 11 patients died during 3 years follow up period due to adverse pathology they were having.Nepal Journal of Neuroscience 13:3-10, 2016